An investigation of seismicity clustered near the Cordel Field, west central Alberta, and its relation to a nearby disposal well. Issue 4 (29th April 2014) - Schultz, Ryan; Stern, Virginia; Gu, Yu Jeffrey
Abstract Historically, seismicity documented in the Western Canada Sedimentary Basin has been relatively quiescent and earthquakes are usually restricted to the foreland belt of the Rocky Mountains. However, exceptional clusters of events, which have remained active for decades, are recognized in Alberta. In this study we investigate the seismicity in this region using data obtained from recently established regional arrays, emphasizing the relationship between a disposal well in the Cordel Field and a nearby cluster of previously reported earthquakes. We explore temporal correlations of wastewater pumping rates and local seismic activity dating back to 1960. We find that the first statistically significant increase in seismicity lags the onset of wastewater injection (October 1991) by ~3.33 years. In particular, the waveform similarity of 32 events are analyzed from continuous data recorded at NOR, a nearby (~30 km) station operated by the University of Alberta starting in September of 2006. Results from this analysis suggest that many events are well correlated in the characteristics of the waveforms and thus are likely to share a similar origin and source mechanism. The most prolific of these multiplets repeats more than 10 times sporadically throughout the entire duration of recorded data from October 2006 to March 2012. Despite the limited availability of nearby stations, which adversely affects the resolution of our analysis, hypocenter depths could be relatively accurately determined from waveform synthesis and double difference methods. The results of our analysis provide first‐order evidence that the seismicity is consistent with fluid injection‐induced events.